A study on multi drug resistant tuberculosis at Sree Mookambika Institute of Medical Sciences - Solanke, Prashant V.; Pawde, Preeti; M., Ajin R. (International Journal Of Community Medicine And Public Health, 2017)
Background: Tuberculosis (TB) is one of the major causes of morbidity and mortality worldwide. Resistance to antitubercular drugs has been noted since the drugs were first introduced, and occasionally outbreaks of drug-resistant tuberculosis have been reported worldwide. WHO emphasizes that good TB control prevents the emergence of drug resistance in the first place and that the proper treatment of multi-drug resistant tuberculosis prevents the emergence of XDR-TB. The objectives of the study were to examine the sputum samples regarding MDR-TB, to study the grading regarding sputum positive and to study the multi-drug resistance tuberculosis in Sree Mookambika Institute of Medical sciences. Methods: Study design was cross-sectional, Study duration was January 2016-March 2017. Study place was Sree Mookambika Institute of Medical Sciences Hospital, Kulasekharam. Sample size was 400. Data entered in MS-Office Word- 2016. Institutional ethical committee clearance was obtained. Results: In present study 54.86% patient had sputum AFB positive, 45.13% had sputum AFB negative smears. 75% of the sputum AFB positive pulmonary TB came under the age group between 20-60 and 25% above 60 yrs. 78.24% males, 21.75% females had sputum AFB smear positive pulmonary tuberculosis and 43.73% patients had positive sputum culture, 56.26% patients had negative sputum culture and the most common strain found was Mycobacterium tuberculosis. Conclusions: So from our study we found that Mycobacterium tuberculosis is the major strain isolated from sputum samples. The resistance is more to Isoniazid and Rifampicin and is more in the rural parts of India. Early screening and drug susceptibility test of culture positive and MTB cases will help in initiating treatment of MDR-TB.